Revisiting the gender gap in commuting through self-employment. (May 2020) - Reuschke, Darja; Houston, Donald
Highlights: The gender commuting gap does not apply to the self-employed. Labour market factors are the main source of the gender commuting gap. Household responsibility and gendered commute preferences explain little of the gender gap in commuting. Longitudinal designs produce different results to much existing literature.